The influence of academic qualifications and professional competence on the career development of elementary school teachers in Tembilahan Hulu district, Indragiri Hilir regency - Linda Melia; Fadly Azhar; Azhar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This research aims to determine the positive and significant influence of teacher academic qualifications (variable X1) and teacher professional competence (variable X2) on teacher career development (variable Y). The research was conducted in Tembilahan Hulu districts, Indragiri Hilir regency state elementary schools. The research was carried out over eight months, from January to August 2023. The population in the research was elementary school teachers in the Tembilahan Hulu district, Indragiri Hilir regency, totalling 178 people, with a sample taken in the research totalling 108 people. The data analysis technique in this research uses qualitative descriptive analysis techniques with percentages and multiple correlation analysis techniques. The research results based on testing the first hypothesis show that teacher academic qualifications influence teacher career development with a significance of Sig 0.00 < 0.05. Then, the second hypothesis test results show that teacher professional competence influences teacher career development with a significance of 0.00 < 0.05. Moreover, the results of the third hypothesis test show a significant influence of teacher academic qualifications and professional competence on teacher career development, with a significance of 0.00 < 0.05. Based on the research results, this research concludes that there is a significant influence between teacher academic qualifications and teacher professional competence on teacher career development